The Role of Religiosity, Social Support, and Cognitive Flexibility in the Subjective Well-Being of Divorced Athlete Women - Eyüp Sarikol; Ramazan Erdoğan; Mir Hamid Salehian (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
Divorce can be an incredibly challenging experience for women, with far-reaching effects on both their personal lives and broader society. Given the significant impact of various factors on an individual's development and adjustment in challenging situations, this study aimed to explore the influence of religiosity, social support, and cognitive flexibility on the subjective well-being of divorced athlete women. This study is descriptive and correlational in nature. The statistical population consisted of all divorced women in Turkiye's Eastern Anatolia Region. To gather data, a sample of 80 divorced female athletes was selected using the convenience sampling method. The data collection tools used in this study consisted of a variety of questionnaires that assessed different aspects. These questionnaires included measures of religious beliefs, social support, cognitive flexibility, subjective happiness, and satisfaction with life. Statistical techniques such as Pearson's correlation and multiple regression analysis were employed to analyse the data. The results revealed a clear correlation between religiosity, social support, cognitive flexibility, and the overall well-being, happiness, and life satisfaction of the participants. In addition, the findings revealed that religiosity, social support, and cognitive flexibility play a crucial role in predicting the subjective well-being of divorced athlete women. These factors accounted for 40% of the variance in the subjects' happiness and life satisfaction. Increasing religiosity, social support, and cognitive flexibility can enhance the happiness and life satisfaction of divorced athlete women.